Skip to main content
replaced http://mathematica.stackexchange.com/ with https://mathematica.stackexchange.com/
Source Link

As a workaround for this incorrect simplification, you could use FindSequenceFunction on a sample of concrete results:

Clear[m,n,k];
Simplify[FindSequenceFunction[
   Table[
    Sum[Binomial[m - 2, k - 1] (k - 1), {k, 2, m, 2}], {m, 2, 12, 2}],
    n] /. n -> m/2]

(* ==> 2^(-4 + m) (-2 + m) *)

This is similar to the answer by @Coolwater herehere.

As a workaround for this incorrect simplification, you could use FindSequenceFunction on a sample of concrete results:

Clear[m,n,k];
Simplify[FindSequenceFunction[
   Table[
    Sum[Binomial[m - 2, k - 1] (k - 1), {k, 2, m, 2}], {m, 2, 12, 2}],
    n] /. n -> m/2]

(* ==> 2^(-4 + m) (-2 + m) *)

This is similar to the answer by @Coolwater here.

As a workaround for this incorrect simplification, you could use FindSequenceFunction on a sample of concrete results:

Clear[m,n,k];
Simplify[FindSequenceFunction[
   Table[
    Sum[Binomial[m - 2, k - 1] (k - 1), {k, 2, m, 2}], {m, 2, 12, 2}],
    n] /. n -> m/2]

(* ==> 2^(-4 + m) (-2 + m) *)

This is similar to the answer by @Coolwater here.

Source Link
Jens
  • 97.6k
  • 7
  • 214
  • 504

As a workaround for this incorrect simplification, you could use FindSequenceFunction on a sample of concrete results:

Clear[m,n,k];
Simplify[FindSequenceFunction[
   Table[
    Sum[Binomial[m - 2, k - 1] (k - 1), {k, 2, m, 2}], {m, 2, 12, 2}],
    n] /. n -> m/2]

(* ==> 2^(-4 + m) (-2 + m) *)

This is similar to the answer by @Coolwater here.